2009
DOI: 10.1242/jeb.030825
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic behaviour of echolocating porpoises during prey capture

Abstract: SUMMARYPorpoise echolocation has been studied previously, mainly in target detection experiments using stationed animals and steel sphere targets, but little is known about the acoustic behaviour of free-swimming porpoises echolocating for prey. Here, we used small onboard sound and orientation recording tags to study the echolocation behaviour of free-swimming trained porpoises as they caught dead, freely drifting fish. We analysed porpoise echolocation behaviour leading up to and following prey capture event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 47 publications
(91 reference statements)
16
112
0
1
Order By: Relevance
“…Previous studies have reported the occurrence of click trains during porpoise foraging behavior, with progressively decreasing ICI's ending in a high rate terminal "buzz", with ICI's close to or less than 2 ms during the fi nal prey capture (Verboom and Kastelein, 2003;DeRuiter et al, 2009;Miller, 2010;Wisniewska et al, 2012). This same echolocation behavior has been suggested for feeding belugas (Roy et al, 2010;Castellote et al, 2013).…”
Section: Acoustic Monitoringsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous studies have reported the occurrence of click trains during porpoise foraging behavior, with progressively decreasing ICI's ending in a high rate terminal "buzz", with ICI's close to or less than 2 ms during the fi nal prey capture (Verboom and Kastelein, 2003;DeRuiter et al, 2009;Miller, 2010;Wisniewska et al, 2012). This same echolocation behavior has been suggested for feeding belugas (Roy et al, 2010;Castellote et al, 2013).…”
Section: Acoustic Monitoringsupporting
confidence: 60%
“…Time intervals between clicks in echolocation click trains, termed interclick intervals (ICI), have been used as a behavioral indicator in several odontocetes, including harbor porpoise (DeRuiter et al, 2009;Verfuss et al, 2009) and beluga (Roy et al, 2010;Castellote et al, 2013). Previous studies have reported the occurrence of click trains during porpoise foraging behavior, with progressively decreasing ICI's ending in a high rate terminal "buzz", with ICI's close to or less than 2 ms during the fi nal prey capture (Verboom and Kastelein, 2003;DeRuiter et al, 2009;Miller, 2010;Wisniewska et al, 2012).…”
Section: Acoustic Monitoringmentioning
confidence: 99%
“…If the ultrasound detector is an energy detector, the threshold can be reached by slow clicking with high sound pressure or fast clicking at lower sound pressure. That feature will accommodate the fact that toothed whales click slowly and with high source levels at long ranges from their prey, but switch to a very fast repetition rate buzzing of lower sound pressure just before prey capture when they are within a body length of the prey (Deruiter et al, 2009;Madsen et al, 2005). With the estimated response energy thresholds one can use the passive sonar equation (Urick, 1983) to estimate at what range an allis shad will be able to detect a toothed whale, for instance a bottlenose dolphin.…”
Section: Discussionmentioning
confidence: 99%
“…To mimic the acoustic exposures from toothed whales at different ranges, we played simulated echolocation click trains with a total duration of 1s at four different repetition rates of 1, 20, 50 and 250clickss -1 (Fig.2C). Approximately 250clickss -1 are emitted from at toothed whale in the final prey capture phase, when it is within a few metres of the prey (Miller et al, 1995;Madsen et al, 2005;Deruiter et al, 2009). Repetition rates of 50clickss -1 and 20clickss -1 mimic a delphinid toothed whale in the approach phase during a prey capture when it would be approximately 10-30 m from the prey (Au, 1993) and a single click could be from scanning toothed whales, that has not locked the biosonar on the prey.…”
Section: Sound Exposurementioning
confidence: 99%
See 1 more Smart Citation